Self-Compassion and Need Frustration Moderate the Effects of Upward Appearance Comparisons on Body Image Discrepancies. Issue 4 (18th May 2020) - Ntoumanis, Nikos; Stenling, Andreas; Quested, Eleanor; Nikitaras, Nikitas; Olson, Jenny; Thøgersen-Ntoumani, Cecilie
Abstract: Drawing from diverse theoretical frameworks, we examined predictors of discrepancy between current and ideal body image in a sample of 396 Greek adolescents. The participants completed assessments of the frequency of comparing oneself with someone of perceived better appearance, appearance evaluations, frustration of basic psychological needs, and appearance self-compassion. We found that upward appearance comparisons negatively predicted appearance evaluation, which in turn was a negative predictor of body image discrepancy. Moderated mediation analyses showed that appearance self-compassion buffered, whereas psychological need frustration augmented the negative effects of upward comparisons on appearance evaluation. Our findings contribute to the growing literature on body image discrepancies in adolescence by examining moderating factors that amplify or buffer such discrepancies, hence identifying viable intervention pathways.